Increased subcortical oligodendroglia‐like cells in pharmacoresistant focal epilepsy in children correlate with extensive epileptogenic zones. (8th November 2016) - Sakuma, Satoru; Halliday, William C.; Nomura, Ruka; Baba, Shiro; Sato, Yosuke; Okanari, Kazuo; Nakajima, Midori; Widjaja, Elysa; Boelman, Cyrus; Ochi, Ayako; Snead, O. Carter; Rutka, James T.; et al.
Summary: Objective: Cortical resections in epilepsy surgery tend to involve multiple lobes in children, compared to adults, partly due to underlying pathology. Oligodendroglia‐like cells (OLCs) have been observed in surgical specimens from children with pharmacoresistant epilepsy. We hypothesize that OLCs recruit multiple‐lobe epileptogenic zones in pediatric pharmacoresistant focal epilepsy. Methods: We examined the surgical specimens from 30 children who underwent epilepsy surgery (1.8‐ to 16.9‐years‐old; mean age 9.7 years). Immunohistochemical assays of OLCs were performed using Olig2, which is a marker of OLC. OLC populations in three sites (gray matter, gray–white matter junction, and white matter) were counted. We also performed immunohistochemical staining with neuronal nuclear antigen (NeuN) and glial fibrillary acidic protein (GFAP) for neuronal and astroglial markers, respectively. NeuN‐ and GFAP‐positive cells were distinguished from OLCs. OLC results were compared with seizure types, scalp and intracranial video–electroencephalography (EEG), magnetic resonance imaging (MRI), surgical resection area, histopathologic diagnosis, and seizure outcome. Results: Histopathologic diagnosis consisted of 14 cases of focal cortical dysplasia (FCD; type I; 4, type II; 9, type III; one); 6 cases of oligodendrogliosis; 6 cases of astrocytic gliosis; 2 cases of hyaline protoplasmic astrocytopathy; and 2 cases of tuberous sclerosis. Fifteen children (50%) underwent multiple‐lobe resections after intracranial video‐EEG. There was a positive correlation between the number of resected electrodes and the OLC population in the white matter (correlation coefficient 0.581, p = 0.001) and at the gray–white matter junction– (correlation coefficient 0.426, p = 0.027). OLC populations in both areas were increased significantly in nine children with epileptic spasms (ES) (gray–white matter junction [p = 0.021] and white matter [p = 0.025]), and nine nonfocal ictal scalp EEG findings (gray–white matter junction [p = 0.04] and white matter [p = 0.042]). The OLC population in white matter was significantly increased in children with 11 nonfocal interictal scalp EEG findings (p = 0.01), with 15 multiple‐lobe resections (p = 0.028). Significance: Pharmacoresistant epilepsy in children with increased OLCs presented with nonfocal epileptiform discharges on scalp EEG and ES, and they required multiple‐lobe resections. We found increased populations of subcortical OLCs in the extensive epileptogenic zone.